2021
DOI: 10.2500/aap.2021.42.210025
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the treatment burden of injectable medication for hereditary angioedema

Abstract: Hereditary angioedema (HAE) is a rare, chronic disease characterized by debilitating swelling episodes in various parts of the body. Patients experience significant burdens related to the symptoms and management of HAE, which can affect their daily lives and reduce their overall quality of life. Prophylactic treatment options have expanded in the past decade to the benefit of patients; however, these therapies require scheduled injections, which can be painful, burdensome, and time consuming. We conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Prophylactic therapeutic options have grown in the past two decades to include lanadelumab (Takhzyro), SC C1-INH (Haegarda), and IV C1-INH (Cinryze). All these treatment options are either large biologics or peptides that must be administered via injection or infusion leading to a significant treatment burden; therefore, the development of an oral long-term prophylactic therapy could increase convenience and improve the ease of administration, reducing treatment burden and improving the quality of life (QoL) in patients with HAE . No oral drugs have been approved for the prevention or treatment of HAE, though a few small molecule PKal inhibitors have been reported. We report the discovery of Berotralstat (BCX7353), an orally bioavailable small molecule PKal inhibitor that has been effective in preventing HAE attacks and has recently been approved by the U.S. Food and Drug Administration (FDA), Japan’s Ministry of Health, Labor, and Welfare (MHLW), and the European Commission for the prophylactic treatment of HAE in patients 12 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic therapeutic options have grown in the past two decades to include lanadelumab (Takhzyro), SC C1-INH (Haegarda), and IV C1-INH (Cinryze). All these treatment options are either large biologics or peptides that must be administered via injection or infusion leading to a significant treatment burden; therefore, the development of an oral long-term prophylactic therapy could increase convenience and improve the ease of administration, reducing treatment burden and improving the quality of life (QoL) in patients with HAE . No oral drugs have been approved for the prevention or treatment of HAE, though a few small molecule PKal inhibitors have been reported. We report the discovery of Berotralstat (BCX7353), an orally bioavailable small molecule PKal inhibitor that has been effective in preventing HAE attacks and has recently been approved by the U.S. Food and Drug Administration (FDA), Japan’s Ministry of Health, Labor, and Welfare (MHLW), and the European Commission for the prophylactic treatment of HAE in patients 12 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the availability of published data on HAE treatment patterns also varies among countries (Figure 2). For example, six studies on the treatments received by patients with HAE and two studies on HAE treatments prescribed by the physicians in the United States included data from up to 1429 patients with HAE and up to 156 physicians treating HAE per study 36–43 . In contrast, we have found only one study from the continent of Africa reporting on HAE treatment patterns; this study included 43 patients with HAE from South Africa 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the studies from United States reported established use of first‐line HAE treatment options, with the use of C1‐INH reported in up to 60.7% of patients and the use of lanadelumab (since 2018) reported in up to 53.3% of patients in separate studies 37–42 . Widespread use of C1‐INH was also reported in Canada (93.5% of physicians reported prescribing C1‐INH for LTP), 64 Germany (ongoing LTP and/or STP with C1‐INH reported in up to 65.0% of patients), 65 and Puerto Rico (LTP with C1‐INH reported in up to 68.7% patients who were taking prophylaxis) 66 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Many patients with HAE report having an informal caregiver, most commonly a family member with HAE, who assists in their HAE‐related medical care. 13 , 14 Patients with HAE can also experience burdens related to repetitive long‐term injectable treatments such as lanadelumab and C1‐INH‐SC, which are administered subcutaneously and can be burdensome, inconvenient, and associated with injection‐site reactions. 9 , 10 , 15 In a 2018 report by the Center for Biologics Evaluation and Research and the U.S. Food and Drug Administration, patients with HAE considered the route of treatment administration to be an important factor in making treatment decisions, with oral preferred over subcutaneous (SC) administration and SC preferred over intravenous.…”
Section: Introductionmentioning
confidence: 99%